Mitigatation of Triplen Harmonics in Distribution System Using Zig-Zag Transformer - Omar, Rosli; Ahmad, Azhar; Sulaiman , Marizan (2006)
This paper studies an application of wye- zigzag transformes for reducing harmonics in the neutral conducto.rs of a three phase 41512.40V distribution system. Triplen harmonic currents add up in the neutral conductor of the distribution system feeding the non linear loads such as personal computers and electronic office machines with switch mode power supplies. The zigzag transformer is installed between the distribution panel and the high harmonics producing loads. This research makes use of a star-zigzag grounded transformer.